Evaluation of goat (Capra hircus) meat or chevon on longanisa - Yap, Ana Maria Cura; De Leon, Sonia Y. (1986.)
In the first phase of the study, an acceptable formulation of chevon longanisa was developed. Five longanisa recipes using chevon, namely Fresh Native Sausage, Country Sausage, Chorizo de Jamon, Chorizo de Recado and Kapampangan Longanisa were prepared and evaluated. The respective sensory evaluation results on a 9 - point hedonic scale were 4.9, 5.5, 5.7, 4.2, and 7.6. The Kapampangan formulation was the most preferred. This recipe was then used to determine the most acceptable lean-fat ratio. Three formulations, with 50%-50%, 60%-40% and 70%-30% lean-fat ratios were made and evaluated. The general acceptability scores were 6.6, 7.3, and 7.3 respectively. The 60%-40% lean to fat combination was found to be most acceptable. In Phase II, 5-kg, 10-kg and 15-kg batches of the Kapampangan formulation with 60%-40% lean-fat ratio using chevon lean and porkfat were made. Multiple comparison showed no significant difference among samples from the three batches. physico-chemcal tests of the 15-kg standardized formulation showed 23% fat, 15% protein, 46.0% moisture, 12% water-holding capacity and a pH of 6. In Phase III, quantitative descriptive analysis by a panel of 15 semi-trained judges showed that chevon and pork longanisa did not differ in color, texture and flavor, although chevon longanisa was rated 'like slightly' (6.7) while pork longanisa was rated 'like moderately' (7.2). Preference ranking tests showed chevon longanisa to be less preffered to pork longanisa.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat -- Preservation; Chevon